Shortage of pathologists in Italy: survey of students and residents - D’Abbronzo, Giuseppe; Lucà, Stefano; Carraturo, Emma; Franco, Renato; Ronchi, Andrea (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
Objective. In Italy, shortage of pathologists is a problem that affects the quality of the National Health System (NHS). The cause of the shortage of pathologists in Italy must be sought in the lack of interests in the pathologist career by Medical Course Students (MCS) and in drop out of Post-Graduate Medical Schools (PGMS). We investigated reasons of both through two surveys. Methods. We developed and proposed on Facebook two surveys, one to MCSs attending last years of study and one to Pathology School Residents (PSRs). Survey for MCSs consisted of 10 questions centered on their perception about pathologist activity; survey for PSRs consisted of 8 questions and investigated the most and least appreciated aspects of Italian PGMS. Results. We obtained 500 responses from the MCSs and 51 responses from the PSRs. Our results show that lack of interest of MCS may be due to their incomplete knowledge of the pathologist’s activities. On the other hand, PSR answers show that some teaching aspects should be improved. Conclusions. Our surveys showed that lack of interest of MCS in the pathology career depends on poor knowledge about the real clinical significance of pathology and PSRs believe that Italian PGMS do not meet their interest. One solution could be a renewal of teaching both in the pathology courses for MCS and in PGMS.